Upgrading biocrudes derived from agricultural biomass into advanced biofuels: Perspective from Malaysia - Mostapha, M. (Elsevier Ltd, 2022)
Liquid fuels derived from fossil source took thousands of years to be converted to crude oil and gas. Alternatively, liquid fuel converted from biomass or generally known as biocrudes is an alternative and feasible source that worth to be explored. Nevertheless, converting biomass from its natural solid form to liquid fuels requires proper pre-treatment and upgrading processes to meet standard properties for commercial use. Besides, chemical properties such as oxygen, nitrogen, sulfur, kinetic value, cetane number, vapor pressure, oxidation stability are other crucial indicators to indicate the quality of biocrudes. This review article highlights the current available technologies to convert biomass to biocrudes, biocrudes upgrading approaches, limitations, and challenges to meet fuel standards, as well as related local and international policies for upgrading biocrudes to fuels. It is expected that this review could pave a positive momentum to drive biocrudes production from agricultural biomass for the sustainability of energy resources. Â© 2022 Elsevier Ltd